2014
DOI: 10.1038/srep04676
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cold Field Emission of Large-area Arrays of Vertically Aligned ZnO-nanotapers via Sharpening: Experiment and Theory

Abstract: Large-area arrays of vertically aligned ZnO-nanotapers with tailored taper angle and height are electrodeposited on planar Zn-plate via continuously tuning the Zn(NH3)4(NO3)2 concentration in the electrolyte. Experimental measurements reveal that the field-emission performance of the ZnO-nanotaper arrays is enhanced with the sharpness and height of the ZnO-nanotapers. Theoretically, the ZnO-nanotaper is simplified to a “charge disc” model, based on which the characteristic macroscopic field enhancement factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 46 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…10(a) shows plots of lnI ∕E 2 av versus 1∕E av , where E av is the photon-averaged incident electric field. The time-domain field enhancement factor β can be calculated from the slopes of those plots [32,33]. The field enhancement factor in that calculation depends on the assumed height of the tunneling barrier Φ, and convincing agreement between experiment and numerical simulations is obtained for Φ 0.25 0.03 eV [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…10(a) shows plots of lnI ∕E 2 av versus 1∕E av , where E av is the photon-averaged incident electric field. The time-domain field enhancement factor β can be calculated from the slopes of those plots [32,33]. The field enhancement factor in that calculation depends on the assumed height of the tunneling barrier Φ, and convincing agreement between experiment and numerical simulations is obtained for Φ 0.25 0.03 eV [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the ion irradiation significantly reduces threshold voltage of the GO emitter which might be due to the reduction of oxygen at the surface of GO sheets provided more field emission active sites. The field emission characteristics of pristine and irradiated GO sheets can be quantitatively explained using the modified FowlereNordheim (F-N) equation [30,31]. The field emission current can be expressed as:…”
Section: Electron Field Emission Propertiesmentioning
confidence: 99%
“…Common mechanisms for producing an electron beam are thermionic, field and photo emission. A topic of current research centres around large area arrays of pointed field emitters [7][8][9][10][11][12] that offer high brightness, high current density beams having a small spread in energy at low operational temperatures.…”
Section: Introductionmentioning
confidence: 99%